Perbedaan kadar protein C, protein S, dan antitrombin III pada pasien dengan Sindrom Koroner Akut (SKA) di RSUP H. Adam Malik, Medan, Indonesia - Maisyaroh Tiurma Anggraini Saragih; Adi Koesoema Aman; Nizam Akbar (DiscoverSys Inc., 2019)
Background: Acute coronary syndrome (ACS) is a life-threatening condition where coronary artery blockage results from thrombosis and leads to ischemia. Individuals with partial deficiency of protein C, protein S or antithrombin III have been found to play a role in increasing the risk of thrombosis. This study aims to determine differences in levels of protein C, protein S and antithrombin III in patients with ACS.Methods: A cross-sectional study was carried out among 60 patients who were treated at H. Adam Malik General Hospital Medan and had fulfilled the inclusion and exclusion criteria through consecutive sampling techniques. Protein C, protein S and antithrombin III were examined with Coatron A4. Bivariate analysis was used to determine differences in the mean levels of protein C, protein S, and antithrombin III in ACS compared with healthy controls. Data were analyzed using SPSS version 17 for Windows.Results: There were a significant difference in S protein levels between the STEMI, NSTEMI, and control groups (P <0.05). S protein levels in the STEMI group were significantly lower compared to NSTEMI and control (P <0.05). However, there were no significant differences in levels of protein C and AT-III between the STEMI, NSTEMI and control groups (P> 0.05).Conclusion: There were no significant differences in ATIII and protein C levels between the STEMI, NSTEMI, and ATIII groups. However, in the S protein parameter, the S protein level was significantly different between STEMI, NSTEMI and the control group.